The Supreme Court and McCarthy-Era Repression : One Hundred Decisions - Lichtman, Robert M., 1933- (Book collections on Project MUSE., 2012)
In this volume, attorney Robert M. Lichtman provides a comprehensive history of the U.S. Supreme Court's decisions in "Communist" cases during the McCarthy era. Lichtman shows the Court's vulnerability to public criticism and attacks by the elected branches during periods of political repression. The book describes every Communist-related decision of the era (none is omitted), placing them in the context of political events and revealing the range and intrusiveness of McCarthy-era repression._x000B__x000B_In Fred Vinson's term as chief justice (1946-53), the Court largely rubber-stamped government action against accused Communists and "subversives." After Earl Warren replaced Vinson as chief justice in 1953, however, the Court began to rule against the government in "Communist" cases, choosing the narrowest of grounds but nonetheless outraging public opinion and provoking fierce attacks from the press and Congress. Legislation to curb the Court flooded Congress and seemed certain to be enacted. The Court's situation was aggravated by its 1954 school-desegregation decision, Brown v. Board of Education, which led to an anti-Court alliance between southern Democrats and anti-Communists in both parties. Although Lyndon Johnson's remarkable talents as Senate majority leader saved the Court from highly punitive legislation, the attacks caused the Court to retreat, with Felix Frankfurter leading a five-justice majority that decided major constitutional issues for the government and effectively nullified earlier decisions. Only after August 1962, when Frankfurter retired and was replaced by Arthur Goldberg, did the Court again begin to vindicate individual rights in "Communist" cases--its McCarthy era was over._x000B__x000B_Demonstrating keen insight into the Supreme Court's inner workings and making extensive use of the justices' papers, Lichtman examines the dynamics of the Court's changes in direction and the relationships and rivalries among its justices, including such towering figures as Hugo Black, Felix Frankfurter, Earl Warren, William O. Douglas, and William J. Brennan, Jr. The Supreme Court and McCarthy-Era Repression: One Hundred Decisions tells the entire story of the Supreme Court during this unfortunate period of twentieth-century American history._x000B_